The Icelandic (Pilot) Project in ScanDiaSyn - Thráinsson, Höskuldur; Angantýsson, Ásgrímur; Svavarsdóttir, Ásta; Eythórsson, Thórhallur; Jónsson, Jóhannes Gísli (Nordlyd, 2007)
In this paper we outline the Icelandic research plans in the Scandinavian Dialect Syntax project and explain why we have made these plans the way we have. We begin by reporting on a pilot project that was conducted in Iceland 2004-2005, explain its nature and describe the resulting plans. As will be seen, our research project includes the collection and analysis of spoken language corpora (“spontaneous speech” of different kinds), collection of syntactic material by using different elicitation techniques (including written questionnaires and interviews), and the comparison of this material. The spoken language corpora are listed and described in the second section of the paper. In the third section we describe how our present (and future) work relates to some previous work done on syntactic variation in Icelandic (and Faroese) and offer some thoughts on the nature of syntactic variation in general.